Simultaneous Quantification of Ten Active Components in Traditional Chinese Formula Sijunzi Decoction Using a UPLC-PDA Method - Kang An; Guo Jin-rui; Zhang Zhen; Wang Xiao-long (Journal of Analytical Methods in Chemistry)
Sijunzi decoction (SJZT), a traditional Chinese formula (TCMF) consisting of four herbs, has been widely used for the treatment of various gastrointestinal symptoms. However, its modernization process is hindered by the lack of a powerful quality control method that covers the major active components in the formula. The aim of this study was to establish a UPLC method for the quantitative determination of ten active components in Sijunzi decoction including ginsenoside Rg1, Re, Rb1, liquiritin, liquiritigenin, glycyrrhizic acid, atractylenolide I, atractylenolide II, atractylenolide III, and pachymic acid. Separation was achieved using an ACQUITY UPLC BEHC18 column (2.1 mm × 100 mm, 1.7 μm) with a gradient elution program consisting of acetonitrile and 0.1% phosphoric acid solution. The detection wavelengths were set at 203, 254, 222, and 267 nm. The method was validated for linearity, accuracy, precision, limit of detection, and limit of quantification. The validated method was successfully applied to the simultaneous quantification of ten active compounds from several finished batches of SJZT. This validated that UPLC method is expected to provide a new basis for the quality control of SJZT.